Bokrecension: Creative Writing for Critical Thinking. Creating a Discoursal Identity - Hellspong, Lennart (Högre utbildning, 2019)
Helene Edberg Creative Writing for Critical Thinking. Creating a Discoursal Identity Palgrave, Macmillan 2018 .